The concept of user satisfaction in archival institutions - (:unkn) unknown (My University, 2011)
Purpose: The customer is one of the most important elements which lie at the center of service organizations. Moreover, the customer is of strategic importance in directing the service process and determining a final decision on this matter. Therefore, numerous studies have been carried out about the customer, in particular focusing on customer satisfaction. Archival institutions provide information and records services. As service organizations, the customers of archival institutions can be defined as those who make use of the archival institutions for the purpose of research. In this context, the term customer or user is also of importance for archival institutions, and thus, different strategies, methods and techniques should be developed and used in archival institutions to achieve and maintain user satisfaction. This paper aims to put strategies for archival institutions in order to provide user satisfaction. Design/methodology/approach: In this research paper, the concept of user satisfaction in archival organizations is discussed as follows: 60 users of the Ottoman Archives were interviewed in order to determine the satisfaction norms of the archives users. A special survey was created for this process. With the answers that were provided in this survey, it was possible to determine the satisfaction criteria for the users of the Ottoman Archives. Finally, by using the satisfaction criteria, the "Satisfaction norms of archives users" were developed. Findings: The concept of user satisfaction in archival organizations is emphasized in this study; in addition "Satisfaction norms of archives users", which are essential for the satisfaction of the users, have been determined. Originality/value: The paper recommends that archival institutions should consider different variables to gain user satisfaction and in this study, specific norms for archival institutions are produced. © Emerald Group Publishing Limited.
Keywords: Achives users; Archival institution; Archives; Customer satisfaction; Organizations; Satisfaction norms of archives users; User satisfaction